When the emperor was divine - Otsuka, Julie, 1962-; Random House Audio (New York : Random House Audio, 2003)
A story told from five different points of view chronicles the experiences of Japanese Americans caught up in the nightmare of the World War II internment camps
Read by : Elaina Erika Davis
Keywords: World War, 1939-1945 -- California -- Fiction; Audiobooks